1999
DOI: 10.1074/jbc.274.25.17742
|View full text |Cite
|
Sign up to set email alerts
|

Aldolase Mediates the Association of F-actin with the Insulin-responsive Glucose Transporter GLUT4

Abstract: To identify potential proteins interacting with the insulin-responsive glucose transporter (GLUT4), we generated fusion proteins of glutathione S-transferase (GST) and the final 30 amino acids from GLUT4 (GST-G4) or GLUT1 (GST-G1). Incubation of these carboxylterminal fusion proteins with adipocyte cell extracts revealed a specific interaction of GLUT4 with fructose 1,6-bisphosphate aldolase. In the presence of aldolase, GST-G4 but not GST-G1 was able to co-pellet with filamentous (F)-actin. This interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 36 publications
3
104
1
1
Order By: Relevance
“…More importantly, it has been suggested that aldolase via its interaction with cytoskeleton functions as a scaffolding protein and plays a crucial role in regulated vesicles exocytosis. Indeed, Kao et al (27) provided compelling evidence for a specific role of aldolase in the insulin stimulation of GLUT4 translocation in adipocytes. In this study, we showed evidence for a specific binding of aldolase B to NKCC2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More importantly, it has been suggested that aldolase via its interaction with cytoskeleton functions as a scaffolding protein and plays a crucial role in regulated vesicles exocytosis. Indeed, Kao et al (27) provided compelling evidence for a specific role of aldolase in the insulin stimulation of GLUT4 translocation in adipocytes. In this study, we showed evidence for a specific binding of aldolase B to NKCC2.…”
Section: Discussionmentioning
confidence: 99%
“…Aldolase is also an actin-binding protein that exhibits a dynamic interaction with the cytoskeleton (22,23). Importantly, aldolase interacts with the H ϩ -ATPase (25,26) and GLUT4 (27), two proteins regulated by intracellular trafficking. More importantly, it has been suggested that aldolase via its interaction with cytoskeleton functions as a scaffolding protein and plays a crucial role in regulated vesicles exocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its roles in metabolism, aldolase has been implicated in several so-called moonlighting functions, which are distinct from its metabolic roles. These non-glycolytic functions of aldolase include roles in signal transduction (38 -41), vesicle trafficking (42,43), and cell motility (15,44). As mentioned previously, many of these moonlighting functions may involve the interaction of aldolase with the F-actin cytoskeleton (18,34,35).…”
Section: Discussionmentioning
confidence: 99%